Kinetics of Phenol Degradation Using TiO₂/Zeolite Composite - Andi Eka Kartika; Sumiati Side; Diana Eka Pratiwi; Nur Afni (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Phenol is a hazardous organic pollutant commonly found in industrial wastewater and is difficult to degrade through conventional treatment methods, thus requiring more effective and sustainable approaches. Photocatalytic degradation using TiO₂ has been widely explored; however, its performance is limited by rapid electron–hole recombination and low surface area. Combining TiO₂ with zeolite enhances adsorption capability and increases the availability of active sites, offering a promising strategy to improve photocatalytic efficiency. This study aims to analyze the kinetic behavior of phenol degradation using a TiO₂/zeolite composite and to determine the optimum irradiation time based on a pseudo-first-order kinetic model. Irradiation times of 15, 30, 45, 60, and 75 minutes were applied, and phenol concentrations were measured using UV–Vis spectrophotometry at 270,20 nm. The results show rapid degradation during the first phase (15-30 minutes), with removal efficiency increasing from 83,014% to 87,315%. After 30 minutes, the degradation rate becomes nearly constant, indicating the attainment of photocatalytic dynamic equilibrium. The -ln(Ct/C0) plot reveals two distinct reaction phases: an initial high-rate phase followed by a plateau phase. Therefore, 30 minutes is identified as the most efficient irradiation time, representing the point at which maximum degradation is achieved before the reaction rate significantly decreases. These findings provide meaningful insight into the photocatalytic kinetics of TiO₂/zeolite composites and support their potential application in phenolic wastewater treatment.